Selection of cassava genotypes with low cyanide content adapted to the Caribbean region of Colombia (2018)
Cassava is worldwide considered a staple food for over one billion people, so it has great importance for food security. In Colombia, the highest production (45%) of cassava comes from the sub-humid environment witch yield very low. The selection process favors genotypes with high dry matter productivity through either high FRY or high DMC, but it is very dificult to find genotypes that are outstanding simultaneously for both traits. For this, CORPOICA-CIAT established a phenotypic recurrent selection program for cassava.